Retracted: The effect of Kenya’s free maternal health care policy on the utilization of skilled delivery services and maternal and neonatal mortality rates in public health facilities - Gitobu, Cosmas Mugambi; Gichangi, Peter Bundi; Mwanda, Walter O. (International Journal Of Community Medicine And Public Health, 2017)
The article titled, "The effect of Kenya’s free maternal health care policy on the utilization of skilled delivery services and maternal and neonatal mortality rates in public health facilities", published in the International Journal of Community Medicine and Public Health, Volume 4, Issue 12, 2017, Pages 4431-4439, DOI: http://dx.doi.org/10.18203/2394-6040.ijcmph20175317 is being retracted on author’s request.